Investigating the Relationship Between Cost of IT Investment and Benefits Realized from the IT Project Implementation Within the Public Sector - Bitta, Fredrick; Oboko, Robert; Chepken, Christopher (International Journal of Scientific Research and Management (IJSRM), 2025)
There has been a long history of failed Information Technology (IT) projects within the public sector and various reasons have been attributed to these failures in previous studies. The lack of a shared theoretical  foundation explains why scholars have looked at many causes for this failures without tying their findings to a larger theoretical framework. This study therefore sought to investigate the relationship between the cost of major IT investments and the benefits realized thereof within the public sector in Kenya. The research adopted a mixed methodology starting with a qualitative study to anchor the research variables followed by a quantitative study. The variables identified qualitatively for measuring IT benefits realized included return on investments (ROI), customer service delivery and the number of customers served. The Pearson's correlation analysis found a negative correlation between the cost of an IT investment and ROI which meant that as the cost of an IT project increased, the value of the ROI decreased and vice versa. The correlation between both the number of customers, customer service delivery and the independent variable cost of an IT investment was found to be negative and insignificant. The multivariate regression results revealed that cost had a significant negative effect on the ROI. The study found that cost had a significant effect on customer service delivery which meant that a unit increase in cost led to an increase in the level of customer service delivery. Therefore, senior management needs to manage IT costs prudently to maximize ROI  in addition to allocating more funds for implementation of public facing systems.